Pengaruh Penerapan SIPD, Kompetensi SDM dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan Pemerintah Kota Bandung (Survei SKPD Pemkot Bandung) - Handayani, Sukma Ayu; Supriatna, Iyeh (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to determine the effect of implementing local government information systems, human resource competencies and the role of internal audit on the quality of financial reports in each SKPD of the Bandung City Government. The research method used is quantitative method with associative research type. The sample used in this study uses the solvency formula and to determine the respondents use a non-probability sampling technique with a purposive sampling method, namely a sampling technique with certain considerations. The distribution of questionnaires was carried out in 37 SKPD Bandung City Government with the number of respondents namely 100 people in the accounting and finance department. The analysis technique used is multiple linear regression with the help of SPSS 26. The results of this study indicate that the influence of the application of local government information systems (SIPD), competence of human resources (HR) and the role of internal audit simultaneously has a positive and significant effect on the quality of financial reports Bandung City Government.